2019
DOI: 10.1155/2019/4248529
|View full text |Cite
|
Sign up to set email alerts
|

Glycine Protects against Hypoxic-Ischemic Brain Injury by Regulating Mitochondria-Mediated Autophagy via the AMPK Pathway

Abstract: Hypoxic-ischemic encephalopathy (HIE) is detrimental to newborns and is associated with high mortality and poor prognosis. Thus, the primary aim of the present study was to determine whether glycine could (1) attenuate HIE injury in rats and hypoxic stress in PC12 cells and (2) downregulate mitochondria-mediated autophagy dependent on the adenosine monophosphate- (AMP-) activated protein kinase (AMPK) pathway. Experiments conducted using an in vivo HIE animal model and in vitro hypoxic stress to PC12 cells rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 72 publications
1
30
1
Order By: Relevance
“…Therefore, a role of AMPK in hypoxic adaptation seems logical. Indeed, there has been increasing evidence of activation of AMPK acting protectively in hypoxia-associated pathologies, e.g., ischemic injury in heart, brain or guts [26][27][28][29]. By decreasing the cellular ATP consumption, the oxygen demand is also lowered; thus, cellular survival is enhanced [30,31].…”
Section: The Role Of Ampk Under Hypoxiamentioning
confidence: 99%
“…Therefore, a role of AMPK in hypoxic adaptation seems logical. Indeed, there has been increasing evidence of activation of AMPK acting protectively in hypoxia-associated pathologies, e.g., ischemic injury in heart, brain or guts [26][27][28][29]. By decreasing the cellular ATP consumption, the oxygen demand is also lowered; thus, cellular survival is enhanced [30,31].…”
Section: The Role Of Ampk Under Hypoxiamentioning
confidence: 99%
“…In neuronal death caused by chronic cerebral hypoperfusion, it is also found that inhibiting excessive mitophagy could exert neuroprotective effects (87). Similarly, inhibition of AMPK-mediated mitophagy could reduce the ischemic and hypoxic damage of neurons in ischemic hypoxic encephalopathy (88).…”
Section: Inhibiting Mitophagy Reduced Cerebral Ischemic-reperfusion Imentioning
confidence: 99%
“…It seems that the two gelatins act as positive allosteric regulators to enhance the efficiency of the calcium-active receptor, thereby activating CaSR, maintaining intracellular calcium homeostasis, and protecting mitochondrial function. On the other hand, glycine, the most abundant amino acid of the two gelatins, could protect against brain injury by regulating mitochondria-mediated autophagy ( Cai et al, 2019 ). Lower level of iron, manganese, and zinc have been observed in patients with Alzheimer’s disease ( Basun et al, 1991 ).…”
Section: Discussionmentioning
confidence: 99%